Character Education Relation with Spiritual Intelligence in Islamic Education Perspective - Etep Rohana (International Journal of Nusantara Islam, 2018)
This article tries to discuss about character education building in an Islamic education perspective. It is education that forms superior character and human character in terms of intellectual, emotional, and spiritual intelligence. The totality of these three bits of intelligence will shape humans. This article is written using a sociological approach with a descriptive type. The method used is library research. The findings obtained indicate that the concept of character education in Indonesia is education that emphasizes great values originating from Indonesian national culture in the context of fostering the personality of the young generation which includes three aspects, namely moral knowledge, moral attitude, and ethical behavior (decent acting). It is following the objectives of Islamic education, which provides for three physical, spiritual, and reason aspects. Therefore, building complete human resources, in essence, is the development of character and superior human character from the intellectual, emotional, and spiritual side that can actualize the dimensions of intellectual, emotional, and spiritual intelligence holistically in the life.